1960
DOI: 10.1084/jem.111.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Pathogenesis of Acute Inflammation

Abstract: The relation of intravascular fibrin to the leucocytic sticking reaction in ear chambers of rabbits injured by heat was investigated in two ways. First, attempts were made to destroy the thin layer of fibrin believed to coat the surfaces of cells involved in the sticking reaction. Second, white cell sticking was studied after fibrinogen had been removed from the blood stream. The results of these experiments were as follows:— 1. Activation of fibrinolysin in vivo by streptokinase did not impair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1961
1961
1989
1989

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…It was found that the addition of thrombin to plasma obtained from animals after extended defibrinogenation produced a small amount of granular precipitate after the mixtures were allowed to stand at room temperature for 8 to 24 hours. Such prolonged incubation of thrombin with experimental plasma was not done in previous studies (1). Although a fibrin web did not form, this granular material suggested a clottable protein, perhaps an altered form of the fibrinogen-fibrin complex.…”
Section: E~ect Of Defibrinogenation Upon Heparin Activity Within Injumentioning
confidence: 67%
See 4 more Smart Citations
“…It was found that the addition of thrombin to plasma obtained from animals after extended defibrinogenation produced a small amount of granular precipitate after the mixtures were allowed to stand at room temperature for 8 to 24 hours. Such prolonged incubation of thrombin with experimental plasma was not done in previous studies (1). Although a fibrin web did not form, this granular material suggested a clottable protein, perhaps an altered form of the fibrinogen-fibrin complex.…”
Section: E~ect Of Defibrinogenation Upon Heparin Activity Within Injumentioning
confidence: 67%
“…Warfarin sodium ~ (supplied as coumadin sodium) in bulk powdered form was prepared in concentrations of 30 mg/ml in sterile water for intravenous administration. Varidase, s data pertaining to enzyme content may be found with experiments, mixed in pyrogen-free 5 per cent dextrose in water (Baxter Laboratories) was administered by continuou s intravenous infusion at a rate of 25 ml per hour by a technique described earlier (1). Preparation and administration of both thromboplastin and thrombin were as noted before (1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations